Osteonecrosis of the femoral head: current concepts and controversies. - Mulliken, B. D. (University of Iowa, 1993)
Despite many investigations into ON of the femoral head, many issues remain unresolved. The pathogenesis in most cases is only speculative and may involve intravascular factors such as microemboli or extravascular factors such as increased interosseous pressure. MRI has emerged as the diagnostic test of choice for suspected early lesions, and radiographs should be used to diagnose and follow advanced lesions. Bone scanning can be useful for early diagnosis and CT scanning or tomography may help plan surgical procedures. The role of the functional exploration of bone is controversial. The natural history of early lesions is unknown; this makes it difficult to evaluate results of treatment. Radiographic ON will usually progress to collapse and arthrosis if treated nonoperatively. The role of core decompression or other joint preserving operations to prevent collapse is controversial, since the reports of success and complication rates have been extremely variable. These procedures are ineffective if used after radiographic collapse. Total hip replacement is the only satisfactory treatment for advanced symptomatic stages, but is relatively contraindicated in young active patients. Further research is needed to assess the natural history of early ON and evaluate the role of surgery in preventing progression.